Pengaruh Penerapan Self Assessment System, Hukum Pajak, Dan Sanksi Pajak Terhadap Tingkat Kepatuhan Wajib Pajak - Ahmad, Zukhrotun Naima; Ratnawati, Dyah (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this study is to find out how the application of self assessment systems, tax laws, and tax sanctions affects the level of compliance with tax obligations. The sample on this study uses purposive sampling methods as well as valid data of 52 tax obligers. Data processing techniques utilize Partial Least Square through the help of SmartPLS 4 application. The results of this study show that self-assessment systems, tax laws, and tax sanctions have a positive and significant impact on the level of compliance with tax obligations. Implications for this study are the need to maintain policies and incentives from the government in particular the Tax Commission by continuing to include taxpayers in the performance of their tax obligation so that it shows a positive impact for the State.